High-strength steel for hydraulic oil cylinder and preparation process of high-strength steel

By laser cladding on the surface of stainless steel castings with hydraulic cylinders, alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide are used as the cladding raw materials, and nickel-plated carbon fiber cloth is used as the inner reinforcement layer, the problem of insufficient wear and impact resistance of existing steels is solved, and the comprehensive performance of high strength, wear, impact resistance and corrosion resistance is achieved.

CN119592885APending Publication Date: 2025-03-11JIANGSU TIANJIAN HYDRAULIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411817019.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The wear resistance and impact resistance of existing steel for hydraulic cylinders are insufficient and cannot meet actual needs.

Method used

A high-strength steel preparation process for hydraulic cylinders is adopted. By laser cladding on the surface of stainless steel castings, alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide are used as the cladding raw materials, and nickel-plated carbon fiber cloth is used as the inner reinforcement layer to adjust the process parameters of laser cladding.

Benefits of technology

The obtained steel has high surface hardness, excellent wear resistance and impact resistance, and has high corrosion resistance and high practicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses high-strength steel for a hydraulic oil cylinder and a preparation technology of the high-strength steel, and relates to the technical field of rolled steel. According to the scheme, the proportion of alloy powder for laser cladding is adjusted, the alloy powder, nickel-plated carbon fibers and nickel-plated silicon carbide serve as cladding raw materials and are mixed with water glass to be prepared into paste, and the paste is preset to the surface of a stainless steel casting; and meanwhile, according to the scheme, the nickel-plated carbon fiber cloth is used as an inner reinforcing layer, the cladding material and the nickel-plated carbon fiber cloth are laid according to the defined scheme, the finally obtained steel has high surface hardness, the abrasion resistance and the impact resistance are improved, the corrosion resistance of the high-strength steel is very excellent, and practicability is high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of steel materials, in particular to high-strength steel for hydraulic cylinders and a preparation process thereof. Background Art

[0002] The hydraulic cylinder is the actuator in the hydraulic transmission system. It is an energy conversion device that converts hydraulic energy into mechanical energy. It is generally made of aluminum, stainless steel, plastic and other materials. Stainless steel has the advantages of high strength, heat resistance and good chemical stability, and has gradually become the preferred material for industrial production.

[0003] The existing steel on the market has poor wear resistance and its impact resistance cannot meet actual needs. Therefore, in order to be suitable for hydraulic cylinders, this application discloses a high-strength steel for hydraulic cylinders and its preparation process, to prepare a steel with high wear resistance, high strength and excellent impact resistance. Summary of the invention

[0004] The object of the present invention is to provide a high-strength steel for a hydraulic cylinder and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation process of high-strength steel for hydraulic cylinders, comprising the following steps: Step (1): taking a carbon fiber cloth or carbon fiber, placing it in a degreasing agent for ultrasonic treatment for 20 to 30 minutes, successively using dilute hydrochloric acid and deionized water for ultrasonic cleaning, placing it in a roughening solution for roughening for 15 to 20 minutes, then placing it in a sensitizing solution for ultrasonic sensitization for 20 to 30 minutes, and then placing it in an activation solution for activation for 20 to 30 minutes to obtain a pretreated carbon fiber cloth or pretreated carbon fiber; The pretreated carbon fiber cloth or pretreated carbon fiber is placed in a chemical plating solution, and the surface is chemically nickel plated, the nickel plating temperature is 50-55° C., and the nickel plating time is 40-80 min, so as to obtain the nickel-plated carbon fiber cloth or the nickel-plated carbon fiber; Step (2): taking alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide, mixing them, ball milling for 3-4 hours, mixing them with water glass solution after ball milling, stirring them into a paste, and obtaining a cladding material; Step (3) takes a stainless steel casting, polishes the surface, and ultrasonically cleans it with acetone for 20 to 30 minutes. Then, in the order of cladding material-nickel-plated carbon fiber cloth, cladding material and nickel-plated carbon fiber cloth are laid on the stainless steel surface in sequence, cladding material is laid on the surface of the top nickel-plated carbon fiber cloth, and dried at 75 to 85° C. to obtain a preset layer, and laser cladding is performed to obtain the high-strength steel.

[0006] In the more optimized solution, in step (3), the laser cladding process parameters are: laser power is 1000~1300W, scanning speed is 500~600mm / min, argon is the protective gas, the flow rate is 6~8L / min, and the overlap rate is 40%.

[0007] In a more optimized solution, in step (1), the amounts of the components of the chemical plating solution are: 20-30 g / L nickel sulfate, 20-30 g / L sodium hypophosphite, 20-30 mL / L lactic acid, 1-2 g / L sodium dodecylbenzene sulfonate, and the pH is 4.

[0008] In a more optimized solution, in step (2), the chemical components of the alloy powder include, by mass fraction, Co: 22.1~23wt%, Cr: 19.2~20.3wt%, Fe: 20.5~22.4wt%, Ti: 16.7~18.2wt%, and the rest is Ni; among the components during ball milling, the mass proportion of nickel-plated carbon fiber is 2~15wt%, the mass proportion of nickel-plated silicon carbide is 5~20wt%, and the rest is alloy powder.

[0009] In a more optimized solution, in step (3), when the mass ratio of nickel-plated carbon fiber is 4-6wt% and the mass ratio of nickel-plated silicon carbide is 6-8wt%, they are mixed with water glass solution after ball milling to obtain cladding material A; When the mass ratio of nickel-plated carbon fiber is 10-15wt% and the mass ratio of nickel-plated silicon carbide is 15-20wt%, they are mixed with water glass solution after ball milling to obtain cladding material B; At this time, the cladding material laying process is: in the laying order of cladding material A-cladding material B-nickel-plated carbon fiber cloth, cladding material A, cladding material B and nickel-plated carbon fiber cloth are laid on the stainless steel surface in turn, cladding material B is laid on the surface of the top nickel-plated carbon fiber cloth, and dried at 75~85℃ to obtain a preset layer.

[0010] In the more optimized solution, in step (2), the ball milling process is as follows: the ball-to-material ratio is 4:1, the ball milling speed is 300-400 r / min, and a 10-min pause is performed after each 30-min ball milling.

[0011] In a more optimized solution, in step (3), the thickness of a single layer of the cladding material is 0.4-1 mm.

[0012] In a more optimized scheme, in step (1), the preparation steps of nickel-plated silicon carbide are: placing silicon carbide in hydrofluoric acid, roughening it for 10 to 15 minutes, the concentration of the hydrofluoric acid solution is 10%, then placing it in a sensitizing solution for ultrasonic sensitization for 20 to 30 minutes, then placing it in an activation solution for activation for 20 to 30 minutes, and finally placing it in a chemical plating solution for nickel plating to obtain nickel-plated silicon carbide.

[0013] In step (1), the degreasing agent is a mixture of sodium hydroxide, sodium carbonate and sodium phosphate, wherein the concentration of sodium hydroxide is 60 g / L, the concentration of sodium carbonate is 20 g / L and the concentration of sodium phosphate is 40 g / L; the roughening liquid is a mixture of sulfuric acid and ammonium persulfate, wherein the concentration of sulfuric acid is 50 g / L and the concentration of ammonium persulfate is 200 g / L; the sensitizing liquid is a mixture of 15 g / L stannous chloride and 40 mL / L hydrochloric acid; and the activating liquid is a mixture of 0.5 g / L palladium chloride and 10 mL / L hydrochloric acid.

[0014] A more optimized solution is a high-strength steel for a hydraulic cylinder prepared according to any of the preparation processes described above.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The invention discloses a high-strength steel for a hydraulic cylinder and a preparation process thereof. Laser cladding is performed on the surface of a stainless steel casting. The scheme adjusts the alloy powder ratio of the laser cladding, and uses alloy powder, nickel-plated carbon fiber, and nickel-plated silicon carbide as cladding raw materials, which are mixed with water glass to form a paste and pre-placed on the surface of the stainless steel casting. At the same time, the scheme uses nickel-plated carbon fiber cloth as an inner reinforcement layer, and the scheme is limited to laying in the order of cladding material-nickel-plated carbon fiber cloth. The final steel material not only has a higher surface hardness, but also has improved wear resistance and impact resistance. The high-strength steel also has excellent corrosion resistance and high practicality.

[0016] In the present application, the scheme defines the specific formula of the alloy powder as "the chemical components of the alloy powder include: in mass fraction, Co: 22.1~23wt%, Cr: 19.2~20.3wt%, Fe: 20.5~22.4wt%, Ti: 16.7~18.2wt%, and the rest is Ni", and nickel-plated silicon carbide and nickel-plated carbon fiber are added as reinforcing materials. The scheme nickel-plates the surface of silicon carbide and carbon fiber to improve the dispersibility and compatibility of silicon carbide and carbon fiber cloth in the laser cladding system. At the same time, the scheme limits the amount of nickel-plated carbon fiber and nickel-plated silicon carbide to obtain high-strength steel covered with a laser cladding layer with the best wear resistance.

[0017] On this basis, the present application introduces nickel-plated carbon fiber cloth, uses nickel-plated carbon fiber cloth as internal reinforcement material, and discloses two schemes with relatively excellent performance. Scheme 1 is: in the order of cladding material-nickel-plated carbon fiber cloth, cladding material and nickel-plated carbon fiber cloth are laid on the surface of stainless steel in sequence, and the cladding material is laid on the surface of the topmost nickel-plated carbon fiber cloth, dried at 75~85℃ to obtain a preset layer, and laser cladding is performed; at this time, in order to improve the performance of the product steel, the actual operation generally limits the "mass ratio of nickel-plated carbon fiber to 10~15wt%, and the mass ratio of nickel-plated silicon carbide to 15~20wt%"; at this time, the surface of the stainless steel casting is laid from bottom to top in the order of "cladding material-nickel-plated carbon fiber cloth-cladding material-nickel-plated carbon fiber cloth...", and after reaching the target thickness, the cladding material is laid on the topmost layer of nickel-plated carbon fiber cloth.

[0018] The second scheme is: when the mass ratio of nickel-plated carbon fiber is 4~6wt% and the mass ratio of nickel-plated silicon carbide is 6~8wt%, they are mixed with water glass solution after ball milling to obtain cladding material A; when the mass ratio of nickel-plated carbon fiber is 10~15wt% and the mass ratio of nickel-plated silicon carbide is 15~20wt%, they are mixed with water glass solution after ball milling to obtain cladding material B; at this time, the cladding material laying process is: according to the laying order of cladding material A-cladding material B-nickel-plated carbon fiber cloth, cladding material A, cladding material B and nickel-plated carbon fiber cloth are laid on the stainless steel surface in sequence, and cladding material B is laid on the surface of the top nickel-plated carbon fiber cloth, dried at 75~85℃, and a pre-set layer is obtained, and laser cladding is performed. At this time, the surface of the stainless steel casting is laid from bottom to top in the order of "cladding material A-cladding material B-nickel-plated carbon fiber cloth-cladding material A-cladding material B-nickel-plated carbon fiber cloth...", and after reaching the target thickness, cladding material B is laid on the top nickel-plated carbon fiber cloth.

[0019] Among them, under the parameter limitations of Scheme 2, the comprehensive performance of the steel obtained is the most excellent, and the wear resistance and impact resistance are also greatly improved. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In this embodiment, the carbon fiber cloth is a PAN-based 3K carbon fiber cloth with a mesh size of 5 mm×5 mm and a gram weight of 200 g / m 2 ; The carbon fiber is T-700 carbon fiber with a length of 2~3mm; the silicon carbide particle size is 50~60μm; the stainless steel casting is made of 361L stainless steel.

[0022] Embodiment 1: A process for preparing high-strength steel for a hydraulic cylinder, comprising the following steps: Step (1): Take a carbon fiber cloth or carbon fiber, place it in a degreasing agent for ultrasonic treatment for 20 minutes, use dilute hydrochloric acid and deionized water for ultrasonic cleaning in sequence, place it in a roughening solution for roughening for 15 minutes, then place it in a sensitizing solution for ultrasonic sensitization for 30 minutes, and then place it in an activation solution for activation for 30 minutes to obtain a pretreated carbon fiber cloth or pretreated carbon fiber.

[0023] The pretreated carbon fiber cloth or pretreated carbon fiber is placed in a chemical plating solution, and the surface is chemically nickel plated at a nickel plating temperature of 55° C. for a nickel plating time of 60 min to obtain a nickel-plated carbon fiber cloth or a nickel-plated carbon fiber.

[0024] The degreasing agent is a mixture of sodium hydroxide, sodium carbonate and sodium phosphate, wherein the concentration of sodium hydroxide is 60g / L, the concentration of sodium carbonate is 20g / L and the concentration of sodium phosphate is 40g / L. The roughening solution is a mixture of 50g / L sulfuric acid and 200g / L ammonium persulfate; the sensitizing solution is a mixture of 15g / L stannous chloride and 40mL / L hydrochloric acid; the activation solution is a mixture of 0.5g / L palladium chloride and 10mL / L hydrochloric acid. The dosage of each component of the chemical plating solution is: 30g / L nickel sulfate, 25g / L sodium hypophosphite, 25mL / L lactic acid, 1.5g / L sodium dodecylbenzene sulfonate, and the pH is 4.

[0025] The preparation steps of nickel-plated silicon carbide are as follows: placing silicon carbide in hydrofluoric acid, roughening for 15 minutes, the concentration of the hydrofluoric acid solution is 10%, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, then placing it in an activation solution for activation for 30 minutes, and finally placing it in a chemical plating solution, nickel-plating the surface for 40 minutes to obtain nickel-plated silicon carbide.

[0026] Step (2): alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide are mixed and ball-milled for 4 hours. After ball milling, they are mixed with water glass solution and stirred into a paste to obtain a cladding material; the chemical components of the alloy powder include: Co: 22.4wt%, Cr: 19.8wt%, Fe: 21.6wt%, Ti: 16.9wt%, and the rest is Ni. Among the components during ball milling, the mass proportion of nickel-plated carbon fiber is 10wt%, the mass proportion of nickel-plated silicon carbide is 15wt%, and the rest is alloy powder. The ball milling process is: ball-to-material ratio is 4:1, ball milling speed is 300r / min, and pause for 10min after each ball milling for 30min. The volume ratio of pure water glass to water in the water glass solution is 1:3.

[0027] Step (3) Take the stainless steel casting, polish the surface, and ultrasonically clean it with acetone for 30 minutes. Then, in the order of cladding material-nickel-plated carbon fiber cloth, lay the cladding material and nickel-plated carbon fiber cloth on the stainless steel surface in sequence, lay the cladding material on the surface of the top nickel-plated carbon fiber cloth, dry it at 85°C, obtain the preset layer, and laser clad to obtain the high-strength steel. The laser cladding process parameters are: laser power of 1300W, scanning speed of 600mm / min, argon as protective gas, flow rate of 8L / min, and overlap rate of 40%. The single-layer laying thickness of the cladding material is 1.6mm. The total thickness of the cladding material is 11.2mm. Two layers of nickel-plated carbon fiber cloth are laid each time, and 12 layers are laid 6 times. Embodiment 2: A process for preparing high-strength steel for a hydraulic cylinder, comprising the following steps: Step (1): taking a carbon fiber cloth or carbon fiber, placing it in a degreasing agent for ultrasonic treatment for 30 minutes, ultrasonically cleaning it with dilute hydrochloric acid and deionized water in sequence, placing it in a roughening solution for roughening for 20 minutes, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, and then placing it in an activation solution for activation for 30 minutes to obtain a pretreated carbon fiber cloth or pretreated carbon fiber.

[0028] The pretreated carbon fiber cloth or pretreated carbon fiber is placed in a chemical plating solution, and the surface is chemically nickel plated at a nickel plating temperature of 55° C. for a nickel plating time of 60 min to obtain a nickel-plated carbon fiber cloth or a nickel-plated carbon fiber.

[0029] The degreasing agent is a mixture of sodium hydroxide, sodium carbonate and sodium phosphate, wherein the concentration of sodium hydroxide is 60g / L, the concentration of sodium carbonate is 20g / L and the concentration of sodium phosphate is 40g / L. The roughening solution is a mixture of 50g / L sulfuric acid and 200g / L ammonium persulfate; the sensitizing solution is a mixture of 15g / L stannous chloride and 40mL / L hydrochloric acid; the activation solution is a mixture of 0.5g / L palladium chloride and 10mL / L hydrochloric acid. The dosage of each component of the chemical plating solution is: 30g / L nickel sulfate, 25g / L sodium hypophosphite, 25mL / L lactic acid, 1.5g / L sodium dodecylbenzene sulfonate, and the pH is 4.

[0030] The preparation steps of nickel-plated silicon carbide are as follows: placing silicon carbide in hydrofluoric acid, roughening for 15 minutes, the concentration of the hydrofluoric acid solution is 10%, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, then placing it in an activation solution for activation for 30 minutes, and finally placing it in a chemical plating solution, nickel-plating the surface for 40 minutes to obtain nickel-plated silicon carbide.

[0031] Step (2): Take alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide, mix them, ball mill for 4 hours, mix them with water glass solution after ball milling, stir them into a paste, and obtain a cladding material; the chemical components of the alloy powder include: Co: 22.4wt%, Cr: 19.8wt%, Fe: 21.6wt%, Ti: 16.9wt%, and the rest is Ni. Among the components during ball milling, the mass proportion of nickel-plated carbon fiber is 12wt%, the mass proportion of nickel-plated silicon carbide is 18wt%, and the rest is alloy powder. The ball milling process is: ball-to-material ratio is 4:1, ball milling speed is 300r / min, and pause for 10min after each ball milling for 30min. The volume ratio of pure water glass to water in the water glass solution is 1:3.

[0032] Step (3) Take the stainless steel casting, polish the surface, and ultrasonically clean it with acetone for 30 minutes. Then, in the order of cladding material-nickel-plated carbon fiber cloth, lay the cladding material and nickel-plated carbon fiber cloth on the stainless steel surface in sequence, lay the cladding material on the surface of the top nickel-plated carbon fiber cloth, dry it at 85°C, obtain the preset layer, and laser clad to obtain the high-strength steel. The laser cladding process parameters are: laser power of 1300W, scanning speed of 600mm / min, argon as protective gas, flow rate of 8L / min, and overlap rate of 40%. The single-layer laying thickness of the cladding material is 1.6mm. The total thickness of the cladding material is 11.2mm. Two layers of nickel-plated carbon fiber cloth are laid each time, and 12 layers are laid 6 times. Embodiment 3: A process for preparing high-strength steel for a hydraulic cylinder, comprising the following steps: Step (1): taking a carbon fiber cloth or carbon fiber, placing it in a degreasing agent for ultrasonic treatment for 30 minutes, ultrasonically cleaning it with dilute hydrochloric acid and deionized water in sequence, placing it in a roughening solution for roughening for 20 minutes, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, and then placing it in an activation solution for activation for 30 minutes to obtain a pretreated carbon fiber cloth or pretreated carbon fiber.

[0033] The pretreated carbon fiber cloth or pretreated carbon fiber is placed in a chemical plating solution, and the surface is chemically nickel plated at a nickel plating temperature of 55° C. for a nickel plating time of 60 min to obtain a nickel-plated carbon fiber cloth or a nickel-plated carbon fiber.

[0034] The degreasing agent is a mixture of sodium hydroxide, sodium carbonate and sodium phosphate, wherein the concentration of sodium hydroxide is 60g / L, the concentration of sodium carbonate is 20g / L and the concentration of sodium phosphate is 40g / L. The roughening solution is a mixture of 50g / L sulfuric acid and 200g / L ammonium persulfate; the sensitizing solution is a mixture of 15g / L stannous chloride and 40mL / L hydrochloric acid; the activation solution is a mixture of 0.5g / L palladium chloride and 10mL / L hydrochloric acid. The dosage of each component of the chemical plating solution is: 30g / L nickel sulfate, 25g / L sodium hypophosphite, 25mL / L lactic acid, 1.5g / L sodium dodecylbenzene sulfonate, and the pH is 4.

[0035] The preparation steps of nickel-plated silicon carbide are as follows: placing silicon carbide in hydrofluoric acid, roughening for 15 minutes, the concentration of the hydrofluoric acid solution is 10%, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, then placing it in an activation solution for activation for 30 minutes, and finally placing it in a chemical plating solution, nickel-plating the surface for 40 minutes to obtain nickel-plated silicon carbide.

[0036] Step (2): alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide are mixed and ball-milled for 4 hours. After ball milling, they are mixed with water glass solution and stirred into a paste to obtain a cladding material; the chemical components of the alloy powder include: Co: 22.4wt%, Cr: 19.8wt%, Fe: 21.6wt%, Ti: 16.9wt%, and the rest is Ni. Among the components during ball milling, the mass proportion of nickel-plated carbon fiber is 15wt%, the mass proportion of nickel-plated silicon carbide is 20wt%, and the rest is alloy powder. The ball milling process is: ball-to-material ratio is 4:1, ball milling speed is 300r / min, and pause for 10 minutes after each ball milling for 30 minutes. The volume ratio of pure water glass to water in the water glass solution is 1:3.

[0037] Step (3) Take the stainless steel casting, polish the surface, and ultrasonically clean it with acetone for 30 minutes. Then, in the order of cladding material-nickel-plated carbon fiber cloth, lay the cladding material and nickel-plated carbon fiber cloth on the stainless steel surface in sequence, lay the cladding material on the surface of the top nickel-plated carbon fiber cloth, dry it at 85°C, obtain the preset layer, and laser clad to obtain the high-strength steel. The laser cladding process parameters are: laser power of 1300W, scanning speed of 600mm / min, argon as protective gas, flow rate of 8L / min, and overlap rate of 40%. The single-layer laying thickness of the cladding material is 1.6mm. The total thickness of the cladding material is 11.2mm. Two layers of nickel-plated carbon fiber cloth are laid each time, and 12 layers are laid 6 times. Embodiment 4: A process for preparing high-strength steel for a hydraulic cylinder, comprising the following steps: Step (1): taking a carbon fiber cloth or carbon fiber, placing it in a degreasing agent for ultrasonic treatment for 30 minutes, ultrasonically cleaning it with dilute hydrochloric acid and deionized water in sequence, placing it in a roughening solution for roughening for 20 minutes, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, and then placing it in an activation solution for activation for 30 minutes to obtain a pretreated carbon fiber cloth or pretreated carbon fiber.

[0038] The pretreated carbon fiber cloth or pretreated carbon fiber is placed in a chemical plating solution, and the surface is chemically nickel plated at a nickel plating temperature of 55° C. for a nickel plating time of 60 min to obtain a nickel-plated carbon fiber cloth or a nickel-plated carbon fiber.

[0039] The degreasing agent is a mixture of sodium hydroxide, sodium carbonate and sodium phosphate, wherein the concentration of sodium hydroxide is 60g / L, the concentration of sodium carbonate is 20g / L and the concentration of sodium phosphate is 40g / L. The roughening solution is a mixture of 50g / L sulfuric acid and 200g / L ammonium persulfate; the sensitizing solution is a mixture of 15g / L stannous chloride and 40mL / L hydrochloric acid; the activation solution is a mixture of 0.5g / L palladium chloride and 10mL / L hydrochloric acid. The dosage of each component of the chemical plating solution is: 30g / L nickel sulfate, 25g / L sodium hypophosphite, 25mL / L lactic acid, 1.5g / L sodium dodecylbenzene sulfonate, and the pH is 4.

[0040] The preparation steps of nickel-plated silicon carbide are as follows: placing silicon carbide in hydrofluoric acid, roughening for 15 minutes, the concentration of the hydrofluoric acid solution is 10%, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, then placing it in an activation solution for activation for 30 minutes, and finally placing it in a chemical plating solution, nickel-plating the surface for 40 minutes to obtain nickel-plated silicon carbide.

[0041] Step (2): Take alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide, mix them, ball mill for 4 hours, mix them with water glass solution after ball milling, stir them into a paste, and obtain a cladding material; the chemical components of the alloy powder include: Co: 22.4wt%, Cr: 19.8wt%, Fe: 21.6wt%, Ti: 16.9wt%, and the rest is Ni. The ball milling process is: the ball-to-material ratio is 4:1, the ball milling speed is 300r / min, and the ball milling is paused for 10 minutes after each 30 minutes. The volume ratio of pure water glass to water in the water glass solution is 1:3.

[0042] When the mass ratio of nickel-plated carbon fiber is 4wt% and the mass ratio of nickel-plated silicon carbide is 8wt%, they are mixed with water glass solution after ball milling to obtain cladding material A; when the mass ratio of nickel-plated carbon fiber is 15wt% and the mass ratio of nickel-plated silicon carbide is 20wt%, they are mixed with water glass solution after ball milling to obtain cladding material B.

[0043] Step (3) Take the stainless steel casting, polish the surface, and ultrasonically clean it with acetone for 30 minutes. Then, in the order of laying cladding material A-cladding material B-nickel-plated carbon fiber cloth, lay cladding material A, cladding material B and nickel-plated carbon fiber cloth on the stainless steel surface in sequence, lay cladding material B on the surface of the top nickel-plated carbon fiber cloth, dry at 85°C to obtain a preset layer; laser clad to obtain the high-strength steel. The laser cladding process parameters are: laser power of 1300W, scanning speed of 600mm / min, argon as protective gas, flow rate of 8L / min, and overlap rate of 40%. The single-layer laying thickness of cladding material A is 0.6mm. The single-layer laying thickness of cladding material B is 1.1mm, and the total thickness of the cladding material is 11.3mm. Two layers of nickel-plated carbon fiber cloth are laid each time, and 12 layers are laid 6 times in total.

[0044] Comparative Example 1: Example 4 was used as the control group. In Comparative Example 1, only conventional carbon fiber cloth was used, and the other processes remained unchanged.

[0045] A preparation process of high-strength steel for hydraulic cylinders, comprising the following steps: Step (1): Take carbon fiber, place it in a degreasing agent for ultrasonic treatment for 30 minutes, use dilute hydrochloric acid and deionized water for ultrasonic cleaning in sequence, place it in a roughening solution for roughening for 20 minutes, then place it in a sensitizing solution for ultrasonic sensitization for 30 minutes, and then place it in an activation solution for activation for 30 minutes to obtain pretreated carbon fiber.

[0046] The pretreated carbon fiber is placed in a chemical plating solution, and the surface is chemically nickel plated. The nickel plating temperature is 55° C. and the nickel plating time is 60 min to obtain nickel-plated carbon fiber.

[0047] The degreasing agent is a mixture of sodium hydroxide, sodium carbonate and sodium phosphate, wherein the concentration of sodium hydroxide is 60g / L, the concentration of sodium carbonate is 20g / L and the concentration of sodium phosphate is 40g / L. The roughening solution is a mixture of 50g / L sulfuric acid and 200g / L ammonium persulfate; the sensitizing solution is a mixture of 15g / L stannous chloride and 40mL / L hydrochloric acid; the activation solution is a mixture of 0.5g / L palladium chloride and 10mL / L hydrochloric acid. The dosage of each component of the chemical plating solution is: 30g / L nickel sulfate, 25g / L sodium hypophosphite, 25mL / L lactic acid, 1.5g / L sodium dodecylbenzene sulfonate, and the pH is 4.

[0048] The preparation steps of nickel-plated silicon carbide are as follows: placing silicon carbide in hydrofluoric acid, roughening for 15 minutes, the concentration of the hydrofluoric acid solution is 10%, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, then placing it in an activation solution for activation for 30 minutes, and finally placing it in a chemical plating solution, nickel-plating the surface for 40 minutes to obtain nickel-plated silicon carbide.

[0049] Step (2): Take alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide, mix them, ball mill for 4 hours, mix them with water glass solution after ball milling, stir them into a paste, and obtain a cladding material; the chemical components of the alloy powder include: Co: 22.4wt%, Cr: 19.8wt%, Fe: 21.6wt%, Ti: 16.9wt%, and the rest is Ni. The ball milling process is: the ball-to-material ratio is 4:1, the ball milling speed is 300r / min, and the ball milling is paused for 10 minutes after each 30 minutes. The volume ratio of pure water glass to water in the water glass solution is 1:3.

[0050] When the mass ratio of nickel-plated carbon fiber is 4wt% and the mass ratio of nickel-plated silicon carbide is 8wt%, they are mixed with water glass solution after ball milling to obtain cladding material A; when the mass ratio of nickel-plated carbon fiber is 15wt% and the mass ratio of nickel-plated silicon carbide is 20wt%, they are mixed with water glass solution after ball milling to obtain cladding material B.

[0051] Step (3) Take the stainless steel casting, polish the surface, and ultrasonically clean it with acetone for 30 minutes. Then, in the order of laying cladding material A-cladding material B-carbon fiber cloth, lay cladding material A, cladding material B and carbon fiber cloth on the stainless steel surface in sequence, lay cladding material B on the surface of the top carbon fiber cloth, dry at 85°C to obtain a preset layer; laser clad to obtain the high-strength steel. The laser cladding process parameters are: laser power of 1300W, scanning speed of 600mm / min, argon as protective gas, flow rate of 8L / min, and overlap rate of 40%. The single-layer laying thickness of cladding material A is 0.6mm. The single-layer laying thickness of cladding material B is 1.1mm, and the total thickness of the cladding material is 11.3mm. Two layers of carbon fiber cloth are laid each time, and 12 layers are laid 6 times in total. Comparative Example 2: Example 4 was used as the control group. In Comparative Example 2, only nickel-plated silicon carbide was used, and nickel-plated carbon fiber was not introduced. The other processes remained unchanged.

[0052] A preparation process of high-strength steel for hydraulic cylinders, comprising the following steps: Step (1): Take a carbon fiber cloth, place it in a degreasing agent for ultrasonic treatment for 30 minutes, use dilute hydrochloric acid and deionized water for ultrasonic cleaning in sequence, place it in a roughening solution for roughening for 20 minutes, then place it in a sensitizing solution for ultrasonic sensitization for 30 minutes, and then place it in an activation solution for activation for 30 minutes to obtain a pretreated carbon fiber cloth.

[0053] The pretreated carbon fiber was placed in a chemical plating solution, and the surface was chemically nickel plated at a nickel plating temperature of 55° C. for 60 min to obtain a nickel-plated carbon fiber cloth.

[0054] The degreasing agent is a mixture of sodium hydroxide, sodium carbonate and sodium phosphate, wherein the concentration of sodium hydroxide is 60g / L, the concentration of sodium carbonate is 20g / L and the concentration of sodium phosphate is 40g / L. The roughening solution is a mixture of 50g / L sulfuric acid and 200g / L ammonium persulfate; the sensitizing solution is a mixture of 15g / L stannous chloride and 40mL / L hydrochloric acid; the activation solution is a mixture of 0.5g / L palladium chloride and 10mL / L hydrochloric acid. The dosage of each component of the chemical plating solution is: 30g / L nickel sulfate, 25g / L sodium hypophosphite, 25mL / L lactic acid, 1.5g / L sodium dodecylbenzene sulfonate, and the pH is 4.

[0055] The preparation steps of nickel-plated silicon carbide are as follows: placing silicon carbide in hydrofluoric acid, roughening for 15 minutes, the concentration of the hydrofluoric acid solution is 10%, then placing it in a sensitizing solution for ultrasonic sensitization for 30 minutes, then placing it in an activation solution for activation for 30 minutes, and finally placing it in a chemical plating solution, nickel-plating the surface for 40 minutes to obtain nickel-plated silicon carbide.

[0056] Step (2): Take alloy powder and nickel-plated silicon carbide and mix them, ball mill for 4 hours, mix them with water glass solution after ball milling, stir and adjust them into a paste to obtain a cladding material; the chemical components of the alloy powder include: Co: 22.4wt%, Cr: 19.8wt%, Fe: 21.6wt%, Ti: 16.9wt%, and the rest is Ni. The ball milling process is: ball-to-material ratio is 4:1, ball milling speed is 300r / min, and pause for 10 minutes after each ball milling for 30 minutes. The volume ratio of pure water glass to water in the water glass solution is 1:3.

[0057] When the mass ratio of nickel-plated silicon carbide is 12wt%, it is mixed with a water glass solution after ball milling to obtain cladding material A; when the mass ratio of nickel-plated silicon carbide is 35wt%, it is mixed with a water glass solution after ball milling to obtain cladding material B.

[0058] Step (3) Take the stainless steel casting, polish the surface, and ultrasonically clean it with acetone for 30 minutes. Then, in the order of laying cladding material A-cladding material B-nickel-plated carbon fiber cloth, lay cladding material A, cladding material B and nickel-plated carbon fiber cloth on the stainless steel surface in sequence, lay cladding material B on the surface of the top nickel-plated carbon fiber cloth, dry at 85°C to obtain a preset layer; laser clad to obtain the high-strength steel. The laser cladding process parameters are: laser power of 1300W, scanning speed of 600mm / min, argon as protective gas, flow rate of 8L / min, and overlap rate of 40%. The single-layer laying thickness of cladding material A is 0.6mm. The single-layer laying thickness of cladding material B is 1.1mm, and the total thickness of the cladding material is 11.3mm. Two layers of nickel-plated carbon fiber cloth are laid each time, and 12 layers are laid 6 times in total.

[0059] Detection experiment: 1. According to the method disclosed in Examples 1 to 4 and Comparative Examples 1 to 2, a high-strength steel sample was prepared. The size of the high-strength steel sample was 15 mm × 15 mm. The wear resistance was tested using an MS-T3000 friction tester. The load was 200 g, the wear radius was 4.5 mm, the test time was 30 min, the rotation speed was 400 rpm, and the friction pair was a silicon carbide ceramic ball with a diameter of 4 mm. The wear volume was recorded after the test. The steel sample was placed in a 5% NaCl solution and soaked for 48 h to observe the surface corrosion resistance.

[0060] The impact resistance of the laser cladding layer was tested. The test sample size was 10mm×10mm×55mm. A non-notched impact specimen was used to test its impact toughness. The average value was taken after 3 to 5 tests.

[0061]

[0062] Conclusion: The present invention adjusts the alloy powder ratio of laser cladding, and uses alloy powder, nickel-plated carbon fiber, and nickel-plated silicon carbide as cladding raw materials, mixes them with water glass to form a paste, and pre-places them on the surface of the stainless steel casting. At the same time, the scheme uses nickel-plated carbon fiber cloth as the inner reinforcement layer, and limits the scheme to be laid in the order of cladding material-nickel-plated carbon fiber cloth. The final steel not only has a higher surface hardness, but also has improved wear resistance and impact resistance. The corrosion resistance of the high-strength steel is also excellent, and it is highly practical.

[0063] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A process for preparing high-strength steel for hydraulic cylinders, characterized in that: The following steps are involved: Step (1): taking a carbon fiber cloth or carbon fiber, placing it in a degreasing agent for ultrasonic treatment for 20 to 30 minutes, successively using dilute hydrochloric acid and deionized water for ultrasonic cleaning, placing it in a roughening solution for roughening for 15 to 20 minutes, then placing it in a sensitizing solution for ultrasonic sensitization for 20 to 30 minutes, and then placing it in an activation solution for activation for 20 to 30 minutes to obtain a pretreated carbon fiber cloth or pretreated carbon fiber; The pretreated carbon fiber cloth or pretreated carbon fiber is placed in a chemical plating solution, and the surface is chemically nickel plated, the nickel plating temperature is 50-55° C., and the nickel plating time is 40-80 min, so as to obtain the nickel-plated carbon fiber cloth or the nickel-plated carbon fiber; Step (2): taking alloy powder, nickel-plated carbon fiber and nickel-plated silicon carbide, mixing them, ball milling for 3-4 hours, mixing them with water glass solution after ball milling, stirring them into a paste, and obtaining a cladding material; Step (3) takes a stainless steel casting, polishes the surface, and ultrasonically cleans it with acetone for 20 to 30 minutes. Then, in the order of cladding material-nickel-plated carbon fiber cloth, cladding material and nickel-plated carbon fiber cloth are laid on the stainless steel surface in sequence, cladding material is laid on the surface of the top nickel-plated carbon fiber cloth, and dried at 75 to 85° C. to obtain a preset layer, and laser cladding is performed to obtain the high-strength steel.

2. The process for preparing high-strength steel for hydraulic cylinder according to claim 1, characterized in that: In step (3), the laser cladding process parameters are: laser power is 1000~1300W, scanning speed is 500~600mm / min, argon is the protective gas, the flow rate is 6~8L / min, and the overlap rate is 40%.

3. The process for preparing high-strength steel for hydraulic cylinder according to claim 1, characterized in that: In step (1), the amounts of the components of the chemical plating solution are: 20-30 g / L nickel sulfate, 20-30 g / L sodium hypophosphite, 20-30 mL / L lactic acid, 1-2 g / L sodium dodecylbenzene sulfonate, and the pH is 4.

4. The process for preparing high-strength steel for hydraulic cylinder according to claim 1, characterized in that: In step (2), the chemical components of the alloy powder include, by mass fraction, Co: 22.1~23wt%, Cr: 19.2~20.3wt%, Fe: 20.5~22.4wt%, Ti: 16.7~18.2wt%, and the rest is Ni; among the components during ball milling, the mass proportion of nickel-plated carbon fiber is 2~15wt%, the mass proportion of nickel-plated silicon carbide is 5~20wt%, and the rest is alloy powder.

5. The process for preparing high-strength steel for hydraulic cylinder according to claim 1, characterized in that: In step (3), when the mass ratio of nickel-plated carbon fiber is 4-6wt% and the mass ratio of nickel-plated silicon carbide is 6-8wt%, they are mixed with water glass solution after ball milling to obtain cladding material A; When the mass ratio of nickel-plated carbon fiber is 10-15wt% and the mass ratio of nickel-plated silicon carbide is 15-20wt%, they are mixed with water glass solution after ball milling to obtain cladding material B; At this time, the laying process is: in the laying order of cladding material A-cladding material B-nickel-plated carbon fiber cloth, cladding material A, cladding material B and nickel-plated carbon fiber cloth are laid on the stainless steel surface in turn, cladding material B is laid on the surface of the top nickel-plated carbon fiber cloth, and dried at 75~85℃ to obtain a preset layer.

6. The process for preparing high-strength steel for hydraulic cylinder according to claim 1, characterized in that: In step (2), the ball milling process is as follows: the ball-to-material ratio is 4:1, the ball milling speed is 300-400 r / min, and a 10-min pause is performed after each 30-min ball milling.

7. The process for preparing high-strength steel for hydraulic cylinder according to claim 1, characterized in that: In step (3), the single layer laying thickness of the cladding material is 0.4~1mm.

8. The process for preparing high-strength steel for hydraulic cylinder according to claim 1, characterized in that: In step (1), the preparation steps of nickel-plated silicon carbide are: placing silicon carbide in hydrofluoric acid, roughening for 10 to 15 minutes, the concentration of the hydrofluoric acid solution is 10%, then placing it in a sensitizing solution for ultrasonic sensitization for 20 to 30 minutes, then placing it in an activation solution for activation for 20 to 30 minutes, and finally placing it in a chemical plating solution for nickel plating to obtain nickel-plated silicon carbide.

9. A high-strength steel for a hydraulic cylinder prepared according to the preparation process according to any one of claims 1 to 8.